Data‐driven adult asthma phenotypes based on clinical characteristics are associated with asthma outcomes twenty years later. Issue 5 (15th January 2019) - Boudier, Anne; Chanoine, Sébastien; Accordini, Simone; Anto, Josep M.; Basagaña, Xavier; Bousquet, Jean; Demoly, Pascal; Garcia‐Aymerich, Judith; Gormand, Frédéric; Heinrich, Joachim; Janson, Christer; Künzli, Nino; et al.
Abstract: Background: Research based on cluster analyses led to the identification of particular phenotypes confirming phenotypic heterogeneity of asthma. The long‐term clinical course of asthma phenotypes defined by clustering analysis remains unknown, although it is a key aspect to underpin their clinical relevance. We aimed to estimate risk of poor asthma events between asthma clusters identified 20 years earlier. Methods: The study relied on two cohorts of adults with asthma with 20‐year follow‐up, ECRHS (European Community Respiratory Health Survey) and EGEA (Epidemiological study on Genetics and Environment of Asthma). Regression models were used to compare asthma characteristics (current asthma, asthma exacerbations, asthma control, quality of life, and FEV1 ) at follow‐up and the course of FEV1 between seven cluster‐based asthma phenotypes identified 20 years earlier. Results: The analysis included 1325 adults with ever asthma. For each asthma characteristic assessed at follow‐up, the risk for adverse outcomes differed significantly between the seven asthma clusters identified at baseline. As compared with the mildest asthma phenotype, ORs (95% CI) for asthma exacerbations varied from 0.9 (0.4 to 2.0) to 4.0 (2.0 to 7.8) and the regression estimates (95% CI) for FEV1 % predicted varied from 0.6 (−3.5 to 4.6) to −9.9 (−14.2 to −5.5) between clusters. Change in FEV1 over time did not differ significantly across clusters. Conclusion: Our findings show that the long‐term risk for poor asthma outcomes differed between comprehensive adult asthma phenotypes identified 20 years earlier, and suggest a strong tracking of asthma activity and impaired lung function over time. Abstract : Risk for poor asthma outcomes varied between cluster‐based asthma phenotypes defined 20 years earlier. The clinical prognosis of the cluster‐based asthma phenotypes was stronger as compared to classical phenotypes. There was a tracking of asthma activity and lung function over the life course for each asthma cluster.